Endoplasmic reticulum and lysosomal Ca2+ stores are remodelled in GBA1-linked Parkinson disease patient fibroblasts - Kilpatrick, Bethan S.; Magalhaes, Joana; Beavan, Michelle S.; McNeill, Alisdair; Gegg, Matthew E.; Cleeter, Michael W.J.; Bloor-Young, Duncan; Churchill, Grant C.; Duchen, Michael R.; Schapira, Anthony H.; Patel, Sandip (Cell calcium (Edinburgh), 2016)
•ER Ca2+ signalling is potentiated in PD patient fibroblasts.•Lysosomal Ca2+ signalling is inhibited in PD patient fibroblasts.•Remodelling of Ca2+ stores is age-dependent. Mutations in β-glucocerebrosidase (encoded by GBA1) cause Gaucher disease (GD), a lysosomal storage disorder, and increase the risk of developing Parkinson disease (PD). The pathogenetic relationship between the two disorders is unclear. Here, we characterised Ca2+ release in fibroblasts from type I GD and PD patients together with age-matched, asymptomatic carriers, all with the common N370S mutation in β-glucocerebrosidase. We show that endoplasmic reticulum (ER) Ca2+ release was potentiated in GD and PD patient fibroblasts but not in cells from asymptomatic carriers. ER Ca2+ signalling was also potentiated in fibroblasts from aged healthy subjects relative to younger individuals but not further increased in aged PD patient cells. Chemical or molecular inhibition of β-glucocerebrosidase in fibroblasts and a neuronal cell line did not affect ER Ca2+ signalling suggesting defects are independent of enzymatic activity loss. Conversely, lysosomal Ca2+ store content was reduced in PD fibroblasts and associated with age-dependent alterations in lysosomal morphology. Accelerated remodelling of Ca2+ stores by pathogenic GBA1 mutations may therefore feature in PD.